Contraction alterations in Brugada syndrome; association with life-threatening ventricular arrhythmias. (15th January 2020) - Scheirlynck, Esther; Van Malderen, Sophie; Motoc, Andreea; Lie, Øyvind H.; de Asmundis, Carlo; Sieira, Juan; Chierchia, Gian-Battista; Brugada, Pedro; Cosyns, Bernard; Droogmans, Steven
Abstract: Background: Brugada syndrome (BrS) is characterized by a high risk of sudden cardiac death. The clinical value of deformation imaging in patients with BrS is unknown. We aimed to assess whether echocardiographic speckle tracking parameters differ between: 1) BrS patients and healthy controls, 2) BrS patients with and without life-threatening ventricular arrhythmias. Methods: Left ventricle (LV) and right ventricle (RV) longitudinal strain and mechanical dispersion (MD) were derived from echocardiography at inclusion. Clinical and ECG data were retrospectively assessed. A life-threatening ventricular arrhythmia was defined as an aborted cardiac arrest or sustained ventricular tachyarrhythmia. Results: We included 175 BrS patients and 82 controls. LV and RV longitudinal strain were lower (−18.1 ± 2.6% vs. −18.8 ± 2.0%, p  = 0.01 and − 24.4 ± 5.4% vs. 25.6 ± 3.7%, p  = 0.04), while MD was higher [38 ± 11 ms vs. 33 ± 8 ms, p  = 0.001 and 15 (8–25) ms vs. 11 (6–19) ms, p  = 0.03] in BrS patients compared to controls. BrS patients who experienced a life-threatening ventricular arrhythmia ( n  = 19) had higher LV MD compared to those without events (43 ± 11 ms vs. 37 ± 11 ms, p  = 0.02). An LV MD ≥40 ms was optimally associated with life-threatening ventricular arrhythmias [odds ratio 4.62 (95%CI 1.58–13.50), p  = 0.005]. Conclusions: BrS patients had lower longitudinal strain and more heterogeneous contractions than healthy controls. Furthermore, BrS patients with a history of life-threatening ventricular arrhythmia had more heterogeneous LV contractions than those without. Therefore, LV MD may be a risk marker in BrS and its evaluation in prospective studies is needed. Graphical abstract: Unlabelled Image Highlights: Brugada syndrome patients have an increased risk for sudden cardiac death Selection of candidates for defibrillator implantation is challenging Speckle tracking echocardiography shows contraction alterations in Brugada syndrome Left ventricle mechanical dispersion is higher in arrhythmic Brugada patients Cardiac imaging might improve risk stratification in Brugada syndrome patients